The role of T cell miRNAs for regulatory T cell induction in islet autoimmunity - Martin G. Scherm; Isabelle Serr; Klaus H. Kaestner; Carolin Daniel (Elsevier, 2019)
Background: microRNAs (miRNAs) have emerged as critical contributors to immune regulation and homeostasis, and their dysregulation is involved in the aberrant differentiation and function of T cell subsets. In type 1 diabetes (T1D), the clinically overt disease is preceded by a presymptomatic phase which is marked by the presence of islet autoantibodies while the individual is still normoglycemic. Recent analyses revealed impaired regulatory T (Treg) cell induction from naive CD4+ T cells during this early phase of autoimmunity. Scope of the review: In this review article, we aim to discuss important recent insights into miRNA regulation of immune homeostasis and activation. Specifically, we highlight the role of miRNAs as biomarkers in autoimmunity and T1D as well as the contribution of specific miRNAs and their downstream pathways to the onset and progression of islet immunity. Furthermore, we focus on critical next steps required to establish miRNAs as biomarkers to predict disease onset and progression and as novel targets of future prevention and treatment strategies to control autoimmunity. Major conclusions: Several recent studies have provided considerable insight into the miRNA regulation of immune homeostasis and how dysregulated miRNAs contribute to onset and progression of islet autoimmunity. Specifically, high levels of individual miRNAs such as miR92a and miR181a are involved in impaired Treg induction during the onset of islet autoimmunity, thereby contributing to disease pathogenesis. The recent advancements in the field suggest miRNAs as potential biomarkers for islet autoimmunity and their direct targeting, especially in a T cell-specific manner, could contribute to the reestablishment of immune homeostasis and ultimately interfere with the onset of islet autoimmunity. Keywords: Immune regulation, Islet autoimmunity, Type 1 diabetes, Regulatory T cell, miRNA, Biomarker